PENGGUNAAN BENTUK SMITH UNTUK MENENTUKAN BENTUK KANONIK MATRIKS NORMAL DENGAN ENTRI-ENTRI BILANGAN KOMPLEKS - Thresye Thresye (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2010)
A normal matrix A with complex number entries is a square matrix n x n with the properties of AA A A.    where t A  A  ie tranpose comrade from matrix A. The normal matrix with complex number entries consists of a unitary matrix, the Hermite matrix and Hermite matrix tilt. Normalized matrices that can not be diagonalized can be brought into shape canonical by using row and column operations called Smith Shapes. Form canonical is a matrix that is close to a diagonal matrix.